Analysis of the Difficulties Learning Speaking Skills at Madrasah Tsanawiyah Students Riyadlatul Ulum Batanghari East Lampung - Masrurotul Mahmudah; Abdul Halim; Muhammad Syaifullah; Ikhwan Aziz Q; Hernisawati Hernisawati (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
There are several factors that are very influential in language, namely human cleverness in speaking skills, Maharah al-Kalam is the ability to express articulated sounds or words to express thoughts in the form of ideas, opinions, desires, or feelings to the interlocutor. In a broader sense, speaking is a system of signs that can be heard and seen which utilizes a number of muscles and muscle tissues of the human body to convey thoughts in order to fulfill their needs. In general, maharah al-kalam aims to be able to communicate properly and properly with the language they are learning. Moving on from the problem of learning disabilities that have a big impact on learning can certainly harm teachers and students in receiving the material. In learning Arabic, of course, you really need a lot of training to speak and memorize vocabulary so that there are no difficulties in learning Arabic. Students must also be active in learning. After that the student looked difficult when he spoke Arabic and spoke it and the accuracy of Arabic was not good, Apart from memorizing habitual vocabulary by the student, creating a supportive environment for practicing conversation. With a good language environment, speech can also be intertwined well. Regardless, there are many problems in learning to speak at MTs Riyadlatul ulum which make the lack of maximum learning in speaking skills, students' lack of speaking in speaking and speaking habits can also hinder the learning process to speak, unclear pronunciation and tarkibnya arrangement make the speaker and listener make it difficult. The population in this study were students of class VIII MTs Riyadlatul Ulum, using qualitative descriptive research. Data collection was carried out by means of interviews, observation and documentation. In the interview, to find out the problems that students have experienced and to get data about the factors that influence it, in the researchers' observations the researchers looked at the problems that appeared to students when in learning and documentation for evidence of research implementation.